9x + 2y =0,5 Y - 2x + 3 = 0.

9x=-2y,x=-2/9y.5y-2((-2/9)y)+3=0,5y+4/9y=-3,49/9y=-3,y=-27/49.x=98/243.

9x=-2y,x=-2/9y.5y-2((-2/9)y)+3=0,5y+4/9y=-3,49/9y=-3,y=-27/49.x=98/243.

9x + 2y =0,5 Y - 2x + 3 = 0.

9x=-2y,x=-2/9y.5y-2((-2/9)y)+3=0,5y+4/9y=-3,49/9y=-3,y=-27/49.x=98/243.

9x=-2y,x=-2/9y.5y-2((-2/9)y)+3=0,5y+4/9y=-3,49/9y=-3,y=-27/49.x=98/243.

Solve this system algebraically.

9x + 2y = 5

y - 2x + 3 = 0

9x + 2y = 5

y - 2x + 3 = 0

9x+2y=5

y-2x-3=0 2y-4x=-6

13x=11

x=13/11

y=59/11

so the answer is x=13/11 y=59/11.

y-2x-3=0 2y-4x=-6

13x=11

x=13/11

y=59/11

so the answer is x=13/11 y=59/11.

Didn't find the answer you were looking for?